Dynamic segmented network coding for reliable data dissemination in delay tolerant networks - Deze Zeng; Song Guo; Hai Jin; Leung, V. (2012 IEEE International Conference on Communications (ICC), 2012)
Delay/Disruption Tolerant Network (DTN) differs from the conventional networks in that it has no continuous or contemporaneous connections among wireless nodes. Its inherent characteristic of intermittent connections makes existing routing solutions hardly to be applied directly. Epidemic routing using random linear network coding has been studied and proved as an efficient way for delivering small amount of data. To our best knowledge, we are the first to study high performance reliable transmission for bulk or stream-like data in DTNs. In this paper, we propose a dynamic segmented network coding scheme to efficiently exploit the transmission opportunity that is scarce in DTNs. In particular, we adopt a dynamic segment size control mechanism, which makes the segmentation adapt to the dynamics of the network. The high performance of our proposal is validated by extensive simulations. Several other interesting findings are also observed from the simulation results.